PERENCANAAN ARSITEKTUR JARINGAN LOCAL AREA NETWORK DALAM PENERAPAN LOAD BALANCING MENGGUNAKAN CISCO PACKET TRACER - Farhan Naufal Mubarok; Indrawan Ady Saputro (PT. Hasba Edukasi Mandiri, 2026)
Along with a huge exchange of information. It is necessary to build a computer network to carry information quickly and accurately. Speed and accuracy in sending information are basic requirements in computer networks. The use of the internet does not yet have good network management, including no backup line that can handle it if the internet line is cut off. On the local network side, there is no double line to anticipate the magnitude of network performance every day. To solve the case above the author tried to apply load balancing. Load balancing is a solution that can be applied to distribute network traffic loads evenly, so that network performance remains optimal. The test results above obtained results that can be applied to computer networks, namely providing smoothness in the network system from PC0 to PC1 with these results the network will continue to work normally and provide comfort for users.